Identification of virulence genes from clinical isolates of Methicillin-Resistant Staphylococcus aureus (MRSA) - SARMAD QASSIM MOHAMMAD; HUSSAM SAMI AWAYID; SINDA ZARROUK-MAHJOUB (Society for Indonesian Biodiversity, 2024)
Abstract. Mohammad SQ, Awayid HS, Zarrouk-Mahjoub S. 2024. Identification of virulence genes from clinical isolates of Methicillin-Resistant Staphylococcus aureus (MRSA). Biodiversitas 25: 5083-5093. Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of Staphylococcus aureus that has developed resistance to beta-lactam antibiotics, including penicillin, methicillin, amoxicillin, and oxacillin. This resistance complicates treatment compared to non-resistant strains. While previous studies have defined MRSA phylogeny and transmission in well-resourced settings, this study specifically highlights the effectiveness of five targeted loci analyses (ermA, ermB, ermC, hla-?, and tsst-1) for understanding MRSA evolution in diverse clinical contexts. This study analyzed the phylogenetic relationships among 20 MRSA isolates, which were amplified from the targeted loci. The research focused on the ermA locus in three isolates (A1-A3), the ermB locus in nine isolates (B1 to B9), the ermC locus in six isolates (C1 to C6), the hla-? gene in one isolate (D1), and the tsst-1 gene in one isolate (E1). Genetic diversity was assessed based on the variants identified within these loci. Direct sequencing of the amplified fragments was conducted to detect genetic polymorphisms, and coding variants were translated to evaluate their potential effects on protein function. A phylogenetic tree was constructed to evaluate the associations and distributions of the experimental variables. Sequencing results confirmed that the isolates were S. aureus. The alignment revealed no variants in samples A1-A3, C1-C6, and D1. One variant (176G>A) was found in group B1-B9, resulting in a missense mutation (p.100Ser>Asn). Sample E1 contained a single nucleotide deletion (56C-del). Phylogenetic analysis revealed distinct clades of isolates that corresponded with various clinical and non-clinical sources. The ermA locus proved to be more effective in tracking the evolutionary trajectories of the studied S. aureus isolates compared to the other loci. These findings suggest that ermA markers could be valuable for broader applications in monitoring the evolutionary distributions of bacterial strains across diverse contexts. Further investigation may enhance our understanding of bacterial evolution in various environments.